A Tale of Two Eras: Mining Big Data from Electronic Health Records to Determine Limb Salvage Rates with Podiatry - Schmidt, Brian M.; Holmes, Crystal M.; Ye, Wen; Pop-Busui, Rodica (Current Diabetes Reviews, 2019)
Aims/Hypothesis: Diabetic foot complications remain very prevalent in the US and worldwide, and a major risk for devastating amputations. We evaluated the impact of establishing a fully integrated and specialized Podiatry service into a large tertiary academic health system to implement structured and targeted preventative foot care on limb salvage rates. Methods: Cross-sectional cohorts’ data mining analysis was conducted of all encounters for diabetes and any foot complications between 2000-2005 and 2010-2015, preceding and after full implementation of podiatry service, respectively. The primary outcome was the change in major non-traumatic lower extremity amputations. Secondary outcomes included minor non-traumatic lower extremity amputations, other diabetic foot complications, limb salvage procedures as documented by procedural coding, and location (outpatient, inpatient, ED) of service rendered. Results: We analyzed 100 million patient encounters that met the above criteria. Compared with the initial cohort, integration of specialized podiatry services resulted in a significant decrease in the number of major amputations from 127 to 85/year (p<0.05), and halved the amputations rate from 0.004% to 0.002% (p<0.05). Rates of minor lower extremity amputations remained unchanged (p>0.10), while the rates of preventative procedures including foot ulcer debridement doubled (0.0002% to 0.0004% ; p<0.03). Diagnoses of diabetic foot complications increased significantly (p<0.05) and shifted toward the outpatient setting. Conclusion: Full integration of specialized Podiatry service led to a significant decrease in major amputation rates, supporting teamwork between podiatry and diabetes health-care providers is essential to performing timely diabetic foot complications management, preventative procedures leading to limb salvage, and a shift in the care location.
Keywords: Diabetic foot